2003
DOI: 10.1034/j.1399-302x.2003.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus and Epstein–Barr virus DNA transcription in endodontic symptomatic lesions

Abstract: The present data suggest that HCMV or EBV infections participate in the pathogenesis of periapical symptomatic lesions. Herpesviruses may produce periapical pathosis as a direct result of viral infection and replication, or as a consequence of virally induced impairment of the host defense and subsequent increased virulence of resident bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
2
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 45 publications
6
120
2
10
Order By: Relevance
“…Infection by HCMV and EBV has been more frequently observed in symptomatic lesions (173,174), and an association has been suggested. However, data related to the occurrence of herpesviruses in acute apical abscesses are rather inconclusive.…”
Section: The Host Side Of the Storymentioning
confidence: 99%
“…Infection by HCMV and EBV has been more frequently observed in symptomatic lesions (173,174), and an association has been suggested. However, data related to the occurrence of herpesviruses in acute apical abscesses are rather inconclusive.…”
Section: The Host Side Of the Storymentioning
confidence: 99%
“…The fact that HCMV was detected as a single infection in 24% of all the periapical lesions while no lesions had EBV monoinfection shows that the HCMV endodontic pathogen is perhaps more important. A study by Sabeti and Slots [24] described only one periapical lesion showing EBV monoinfection, while Sabeti et al [25] found HCMV active infection in 92% and EBV infection in 62% of symptomatic periapical lesions. Approximately the same ratio of these two viruses was found by Yildirim et al [26], who examined the presence of herpesvirus in periapical lesions of deciduous teeth.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ferreira et al [18] found EBV in 6% of purulent exudates from acute apical abscesses, whereas they did not identify HCMV in abscess samples using single and nested PCR. The discrepancies in the findings among our study and the three studies mentioned above might arise for several reasons, including differences in the primers used, methods used for DNA extraction, and host and environmental factors such as genetic background, ethnicity, and socioeconomic status [8,[20][21][22][23]. We used same sampling techniques applied by Chen et al [1].…”
Section: Discussionmentioning
confidence: 99%